2022
DOI: 10.3389/fimmu.2022.851622
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Prognostic Risk Model for Cervical Cancer Based on Immune Checkpoint HLA-G-Driven Differentially Expressed Genes

Abstract: Human leukocyte antigen G (HLA-G) is a potential checkpoint molecule that plays a key role in cervical carcinogenesis. The purpose of this study was to construct and validate a prognostic risk model to predict the overall survival (OS) of cervical cancer patients, providing a reference for individualized clinical treatment that may lead to better clinical outcomes. HLA-G-driven differentially expressed genes (DEGs) were obtained from two cervical carcinoma cell lines, namely, SiHa and HeLa, with stable overexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 60 publications
(85 reference statements)
2
9
0
Order By: Relevance
“…[33] Furthermore, MSMO1 is involved in the biosynthesis and metabolism of sterols and cholesterol. [34] Previous studies reported that MSMO1 expression is up-regulated in cervical cancer [35,36] and down-regulated in hepatocellular carcinoma, [37] cholesterol synthesis in chondrocytes, [38] pancreatic cancer, [39] and iron overload, [40] which is consistent with our results. NCOA4 encodes a selective receptor that mediates ferritinophagy and the cytosolic iron storage complex [41,42] and plays a selective regulatory role in the case of iron deficiency or iron overload.…”
Section: Discussionsupporting
confidence: 92%
“…[33] Furthermore, MSMO1 is involved in the biosynthesis and metabolism of sterols and cholesterol. [34] Previous studies reported that MSMO1 expression is up-regulated in cervical cancer [35,36] and down-regulated in hepatocellular carcinoma, [37] cholesterol synthesis in chondrocytes, [38] pancreatic cancer, [39] and iron overload, [40] which is consistent with our results. NCOA4 encodes a selective receptor that mediates ferritinophagy and the cytosolic iron storage complex [41,42] and plays a selective regulatory role in the case of iron deficiency or iron overload.…”
Section: Discussionsupporting
confidence: 92%
“…Loss of HLA can cause inefficient ability of presenting neoantigens to promote immune evasion ( Aptsiauri and Garrido, 2022 ). Expressions of HLA-A, HLA-B, HLA-C, and HLA-G were associated with prognosis of different cancers ( Noblejas-López et al, 2019 ; Michelakos et al, 2022 ; Xu et al, 2022 ). HLA-DRA and HLA-DMA expressions were synergistically related to immune checkpoint blockade efficacy, T-cell rejection, and high risk of recurrence for estrogen receptor (ER)-negative cells ( Liu and Hofman, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given that a large number of established immune-related risk models showed potential utility in guiding immunotherapeutic options ( Li X. et al, 2022 ; Gao et al, 2022 ; Xu et al, 2022 ), we determined to continue our research in this direction. First, the expression levels of 3 commonly-used target genes for immune checkpoint inhibitor (ICI) therapies, CTLA-4, PD-L1 and PD1 were compared between high and low risk patients.…”
Section: Correlation Of Crc Trm Clusters With Biological Function And...mentioning
confidence: 99%